D-galactose Intake Alleviates Atopic Dermatitis in Mice by Modulating Intestinal Microbiota - Kim, Dong-Yeon; Jung, Do-Hyeon; Song, Eun-Jung; Jang, Ah-Ra; Park, Ji-Yeon; Ahn, Jae-Hun; Lee, Tae-Sung; Kim, Yeong-Jun; Lee, Yun-Ji; Seo, In-Su; Kim, Hye-Eun; Ryu, Eun-Ju; et al. (Frontiers in Nutrition, 2022)
Atopic dermatitis (AD) is one of the most prevalent, chronic and persistent inflammatory skin diseases closely associated with intestinal microbiota. To evaluate the effect of D-galactose intake on AD, we orally administered D-galactose to BALB/c mice whose ears and skin were treated with 2,4-dinitrochlorobenzene (DNCB). D-galactose alleviated DNCB-induced AD-like phenotypes such as redness, scaling/dryness and excoriation. Ear thickness was also decreased by D-galactose administration. Histopathological analysis revealed decreased epidermal thickening, infiltration of immune cells, especially mast cells, in the dermis. Total levels of serum IgE representing the immunological response of AD were decreased by D-galactose administration. Microbiota analysis showed that D-galactose administration restored gut microbiota profiles, which were altered in AD mice, characterized by increased abundance of Bacteroidetes and decreased abundance of Firmicutes. The increased abundance of Bacteroides and the decreased abundance of Prevotella and Ruminococcus were reversed by D-galactose treatment, following improvement of AD. Our results suggest the possible use of D-galactose as a prebiotic to alleviate AD by altering gut microbiota.